THE IMPACT OF LEARNING ENGLISH PODCAST (LEP) TOWARD STUDENTS ENGLISH LISTENING SKILL (Study at seventh-grade Student’s of SMPN 11 Bengkulu Tengah, Academic year 2025-2026) - Oktariani, Indri; Riswanto; Efrizal, Dedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low listening skills in English among seventh-grade students at SMPN 11 Bengkulu Tengah. The problems identified include limited use of digital technology in learning, the use of less varied conventional methods, and low student learning motivation which tends to be passive. This study aims to determine the effect of using Learning English Podcast (LEP) on improving the English listening skills of seventh-grade students at SMPN 11 Bengkulu Tengah in the academic year 2025/2026. This study used a quantitative method with a quasi-experimental, nonequivalent control group design. The sample consisted of 40 students selected through purposive sampling, divided into class VII A as the experimental group and class VII B as the control group. The research instrument was a 30-item multiple-choice listening test. The results showed a significant improvement in students' listening ability, indicated by the experimental class post-test mean of 72.25, higher than the control class mean of 43.30. The independent samples t-test showed a significance value of p < 0.001 (sig. 2-tailed < 0.05), indicating a significant difference between the two groups. It can therefore be concluded that the use of Learning English Podcast (LEP) is effective in improving students' English listening skills, particularly in understanding main ideas, specific information, vocabulary, and the meaning of spoken conversation..